Replacing NRA by fast GD-OES measurements as input to a model based prediction of hydrogen diffusion in a-Si. (September 2017) - Steffens, Jonathan; Becker, Hans-Werner; Gerke, Sebastian; Joos, Sebastian; Hahn, Giso; Terheiden, Barbara
Abstract: In order to predict hydrogen diffusion in hydrogenated amorphous silicon (a-Si:H) layers, Gerke et al.[1] proposed a model which requires just one nuclear resonant reaction analysis (NRA) and one Fourier transform infrared spectroscopy (FT-IR) as input. This contribution presents the possibility to substitute this single NRA measurement by a calibrated glow discharge optical emission spectroscopy (GD-OES) measurement. In the hydrogen concentration range of 2-30 at% relevant for a-Si:H layers there are currently no commercial calibration standards available, leading to the necessity of laboratory standards. Hydrogen depth profiles of a-Si:H layers exhibit plateaus of constant hydrogen concentration in a range large enough to qualify them as calibration standards. Therefore, six plasma enhanced physical vapor deposited (PECVD) a-Si:H layers with different hydrogen concentrations were prepared as laboratory standards. The absolute hydrogen concentration was determined using the NRA technique and the layer thickness was determined with a focused ion beam (FIB) in a scanning electron microscope (SEM). These results enabled a calibration of the GD-OES setup for a-Si:H, which successfully reproduced the NRA measurements of Gerke et al. [1].